Identification of temporal factors related to shot performance for indoor recurve archery - Callaway, A. J.; Wiedlack, J.; Heller, M. (Journal of Sports Sciences, 2017)
The purpose of this study was to investigate the temporal phases of the archery shot cycle that distinguish the arrows distance from centre, in an attempt to understand critical factors that affect performance. Fifteen archers of varying ability each performed 30 shots at 18 m. Fourteen potential predictor variables were measured for statistical modelling by stepwise multiple linear regression. The results show that pre-shot time (pre-performance routine), follow-through time (post-performance routine), aiming time, speed of the arrow and the %variation in clicker-release time, account for 7.7% of the variation in predicting shot performance. The results have implications for practice demonstrating factors that coaches should focus on to develop their athletes. Further work on pre-, but more importantly, post-performance routines are needed generally within sport research as they are lacking and have been shown to be important contributing factors in a number of sports.